Analyzing Perception and Hesitation in the Context of Home Science Career Aspirations - Kriti, Komal; Singh, Aarti; Yadav, Akansha; Anshu, (Indian Journal of Extension Education, 2025)
Home science, despite its rich potential for addressing contemporary societal needs, faces hesitation among prospective students as a viable career option. The study conducted in 2024 on 50 students from several Home Science Educational Institutions. This study adopted a descriptive approach, using structured close-ended questionnaires through quantitative analysis involving interviews and surveys to collect information. This study explored the relationship between students’ perceptions of home science as a career option and the factors contributing to their hesitancy in pursuing it. A chi-square analysis was conducted. The findings indicated that stereotypes, peer influence, and confusion about career pathways significantly impact students’ perceptions, contributing to hesitation in choosing home science. Conversely, gender bias, limited career knowledge, uncertainty about job opportunities, and lack of family support did not show significant relationships with students’ perceptions, indicating that these factors were less influential in their decision to consider home science as a viable career option. These findings highlighted the importance of addressing stereotypes and peer pressure while providing clearer career pathways to improve the perception of home science. The study suggested that targeted interventions in these areas could encourage more students to view home science as a rewarding and viable career choice.
Keywords: Home science; Career; Hesitation; Perceptions; Peer influence; Stereotypes